INDIRECT SPEECH ACT IN JUDY CHRISTENBERRYâS NOVEL THE COWBOYâS SECRET SON : A PRAGMATIC ANALYSIS - Muntiningsih, Ratna (Perspective Jurnal Pendidikan Bahasa Inggris, 2013)
This paper presents the core of a descriptive theory of Indirect Speech acts, i.e. uttererances used by the speaker to the hearer based on the three type of felicity conditions such as content condition, preparatory condition, and sincerity condition. The data examples taken from the English novel âThe Cowboyâs Secret Sonâ contains some of indirect speech act uttrances that are included to the pragmatic study. The researcher explains and analyzes every utterance based on the theory of Yule (996), Searle (1976, 1975), Austin (1962), Mey (1993), Bach and Harmish (1979), and Levinson (983). The result of the research is founded that the speaker uses indirect speech act is to convey the request to the hearer to do something in the future. Moreover they use indirect speech act which has two meanings such as literal meaning and non-literal meaning or indirect meanig. In other words, they use indirect speech act to avoid the hearer to get upset, feel bad, angry and for politeness. And, generally they use indirect spech act because they have recognized the matters they are uttering. Keywords: Theme, Rheme, Thematic Progression